ROLE OF NUTRITION IN HUMAN CAPITAL DEVELOPMENT: AN EMPIRICAL STUDY IN THE INDIAN CONTEXT - D R Jalwani; Riyaz Ali; Chaturvedi, Saumya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Health and nutrition form crucial elements of human capital development, where their relationship with human resource development is mutually reinforcing and cyclical. Nutrition, integral to both health and developmental outcomes, receives significant emphasis in the formation of human capital across developed nations today. This process commences during childhood, underscoring its foundational role in modern societal advancement. The physical health of an individual during the early stages of life plays a pivotal role in determining the quality of human capital. Proper nutrition is essential for sustaining and enhancing health, particularly in these formative years. During childhood, nutrition serves as the primary source of essential nutrients, including macronutrients and micronutrients, which are critical for growth and development. Moreover, proper nutrition during early life stages can reduce the risk of non-communicable diseases later in life, laying the foundation for healthier and more productive individuals as they grow. This underscores the importance of ensuring that children receive the necessary nutrients from a young age to promote their overall well-being and long-term human capital development. 213 respondents were considered in the study as a sample size. Mean and T-test was applied in the study to find the outcome.